JPX and LINC00641 ncRNAs expression in prostate tissue: a case-control study - Roshanak S Sajjadi; Mohammad Hossein Modarressi; Mohammad Amin Tabatabaiefar (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Prostate cancer (PC) is the second most prevalent cancer in men. Prostate-specific antigen (PSA) is the main biomarker for screening PC. An increase in PSA could lead to false-positive results. Thus, more appropriate markers should be investigated. In the present study, JPX and LINC00641 expression levels were measured in tumoral prostate tissue compared with the non-tumor tissue. Experimental approach: 43 pairs of prostate tumoral and non-tumor tissue were prepared. The expression levels of JPX and LINC00641 were investigated by RT-qPCR. Findings/Results: Significant upregulation of LINC00641 (2.47 ± 0.5 vs 1.41 ± 0.2) and downregulation of JPX (1.42 ± 0.6 vs 2.83 ± 1.0) were observed in PC tissues compared with the normal tissues (their adjacent non-tumoral tissues). Conclusion and implications: Dysregulation of JPX and LINC00641 in PC patients could be used in the future as a prognostic biomarker in PC.